EFEKTIVITAS PELAYANAN ONLINE APLIKASI MOBILE JKN TERHADAP KEPUASAN PASIEN RAWAT JALAN DI RUMAH SAKIT ISLAM MALAHAYATI MEDAN - Apriliani; Harahap, Aynil Paydah; Muamar, Hafiz; Nisa, Widiya (HEALTH CARE: JURNAL KESEHATAN, 2025)
The use of digital services via the National Health Insurance (JKN) Mobile Application is an initiative to enhance the quality and efficiency of outpatient services. This study is to evaluate the efficacy of the JKN Mobile online service and its correlation with patient satisfaction at Malahayati Islamic Hospital, Medan. The study employed a cross-sectional design, utilizing accidental sampling to identify 60 respondents. The research instrument comprised a standardized questionnaire that evaluated service speed, convenience, internet network quality, and information. Univariate and bivariate analyses were conducted utilizing the Chi-Square test at a significance level of 0.05. The findings indicated that a significant proportion of respondents assessed the service as effective regarding speed (88.3%), convenience (85.0%), and information (80.0%), but 58.3% deemed the internet network inadequate. Patient satisfaction attained 80.0%. Bivariate analysis indicated a significant correlation between service speed and satisfaction (p=0.002; PR=16.429; 95% CI: 2.655–101.643). The ease of service was also significant (p=0.012; PR=7.857; 95% CI: 1.688–36.569). The information on health services exhibited the most significant impact (p=0.000; PR=22.000; 95% CI: 4.543–106.533). Simultaneously, the internet connection approached statistical significance (p=0.050; PR=4.600; 95% CI: 0.910–23.252) and exhibited a less persistent effect compared to the other factors. The findings affirm that process speed, application usability, and information clarity are pivotal in influencing patient happiness, whereas network quality necessitates focused attention to enhance digital service adoption. Hospitals must enhance the clarity of information and the efficiency of Mobile JKN services while improving network quality and internet availability to elevate patient satisfaction.